Graph Visualization and Navigation in Information Visualization: A Survey - Herman, Ivan; Melançon, Guy; Marshall, M. Scott (IEEE Transactions on Visualization and Computer Graphics, 2000)
This is a survey on graph visualization and navigation techniques, as used in information visualization. Graphs appear in numerous applications such as Web browsing, state-transition diagrams, and data structures. The ability to visualize and to navigate in these potentially large, abstract graphs is often a crucial part of an application. Information visualization has specific requirements, which means that this survey approaches the results of traditional graph drawing from a different perspective.